Production of Cocoa Pulp Syrup by Utilizing Local Sugar Sources - Firdaus Firdaus; Reni Desmiarti; Erti Praputri; Amelia Amir (Green Engineering Society, 2022)
The pulp of the cocoa fruit still has not economically viable yet. Its potency to be processed into fruit syrup is expected to increase its value added. Local sugar from palm and canes is still traditionally utilized to produce brown sugar. This study aimed to make fruit syrup by utilizing cocoa pulp and local sugar sources in West Sumatra with several variants (palm sugar, sugarcane, and market white sugar). The effects of sugar concentration on the quality of the syrup were also studied. Sensory evaluation by the hedonic method was performed and statistical analysis data were carried out using SPSS. Microbiological analysis and shelf-life testing also have been done. The results of this study showed that respondents preferred syrup with palm sugar to sugarcane because of its light brown color and distinctive sweetness. The microbiological test reported that the syrup could only be consumed for less than the 5th day in a sealed glass bottle if it was placed at room temperature. Meanwhile, the syrup placed in the refrigerator (5 0C) could keep until the 5th day